Estimation of total Body Water on the basis of Body Weight, Height and Age in University Players: - (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The aim of the study to develop regression equation on basis of Body weight, Height and Ageto predict the Total Body water. Further to find out correlation among selected Independent variables(Body Weight, Height and Age) with Dependent Variable (Total Body water),to study the joint contributionof Independent Variables in estimating Total Body water. Fifty male university players male fromLN.I.P.E,N.E.R.C, Guwahati, Assam. The age ranged from 20 to 27 were selected for this study. Toachieve the objective of present study, Pearson’s Product Moment correlation and multiple correlationswas used. Regression equation (Enter method) was established for predicting Dependent variable on thebasis of Independent variables. There exists a significant relationship between Total Body water Bodyweight (.728), Height (.429), Age (-.382).In regression mode , the value of R2[0.606(Body weight,Height, Age)] developed for prediction of Total Body water. The resulting regression equation isTotal Body water = 19.444 + 0.310 (Body weight) + 0.073 (Height) - 0.583 (Age)